IDENTITAS DIRI DITINJAU DARI KELEKATAN REMAJA PADA ORANG TUA DI SMKN 4 YOGYAKARTA - Muhammad Ali Husni; Indriyati Eko Purwaningsih (JURNAL SPIRITS, 2013)
ABSTRACTThe purpose of this study was to determine the self identity in terms of adolescent attachment to parents in SMKN 4 Yogyakarta. The number of samples used in this study amounted to 130 students of class X SMKN 4 Yogyakarta. The sampling technique used in this study was purposive sampling. The analysis of the data used in this study is the Pearson product moment correlation Results of this study indicate that there is a positive relationship between attachment to parents of adolescent self identity in SMKN 4 Yogyakarta. In a correlation test on adolescent attachment variables to adolescent self identity, there is a significant positive correlation. It can be seen from the coefficient of r = 0.599 with p = 0.000 (p <0,05). For variable self identity among young women and men there was no difference between the two. This can be seen with sig t 0.211 which means> 0.005. and independent simple t test. Â Keywords: self identity, attachment to parents